Coupling vibration behaviors of drum-disk-shaft structures with elastic connection. (May 2019) - Li, Chaofeng; Tang, Qiansheng; Xi, Chenyang; Zhong, Bingfu; Wen, Bangchun
Highlights: A new dynamic model of a rotating drum-disk-shaft structure is established. The disk's vibration and the drum's translational motion is considered. The effect of circumferential number on coupling behaviors of the system is studied. The effect of support and coupling stiffness on dynamic behaviors is studied. The Campbell diagram of the system is investigated. Abstract: The drum-disk-shaft system is a significant part of the aero-engine rotor structure and directly influences the rotor dynamics. The dynamic model of a drum-disk-shaft structure was established considering the elastic support, flexible connection, and the Coriolis and centrifugal effects on the drum due to the rotation. The effects of support stiffness, coupling stiffness and rotating speed on vibration behaviors of the system were investigated. Some results were obtained. It is found that the disk's vibration and the drum's translational motion are coupled whatever the circumferential number ( n ) is, and the local deformation of the drum is coupled with the disk's vibration only under n = 1. When n is equal to 1, the more veering phenomena can be found during the process of the variation of the coupling stiffness, and support stiffness and the mode shapes are plotted to show the phenomena. At last, the effect of rotating speed on the frequencies of the coupling system was investigated. It is shown that the forward and backward traveling waves are generated in all the modes of the system under n = 1 due to the rotating speed and coupling effects, but only in the modes of the drum as n is not equal to 1. Also, the coupling stiffness and support stiffness can significantly affect the critical speed of the system. Graphicalabstract : Image, graphical abstract